2021
DOI: 10.4240/wjgs.v13.i6.574
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis and COVID-19: A literature review

Abstract: BACKGROUND Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the ongoing pandemic of coronavirus disease 2019 (COVID-19), and has caused more than 80 million infections and 1.7 million deaths worldwide. Although it is primarily a respiratory virus, SARS-CoV-2 also has extra-pulmonary effects. Pancreatic injury and cases of acute pancreatitis (AP) have been recognized and attributed to SARS-CoV-2, but the mechanisms of pancreatic injury are still a subject of debate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…A study done by Fan Wang has shown that nine out of 52 patients with COVID 19 infection have pancreatic injury [ 5 ]. Furthermore, approximately 10% of the COVID 19 positive patients may present only with gastrointestinal symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Fan Wang has shown that nine out of 52 patients with COVID 19 infection have pancreatic injury [ 5 ]. Furthermore, approximately 10% of the COVID 19 positive patients may present only with gastrointestinal symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent literature reviews in Correia de Sá T et al [25] and Jabło ńska B et al [26]-where they used a different search approach and included case reports/seriesconcluded that there is still insufficient evidence demonstrating that COVID-19 can cause AP or negatively impact disease prognosis. Ultimately, the most important clinical research questions are how to predict the course of the disease and the overall outcome when COVID-19 and AP coexist.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COVID-19 is also associated with acute pancreatitis. Although the clear pathogenesis is still unknown, it is thought to be from the direct cytotoxic effect of the virus on the exocrine pancreas, secondary to cytokine storm, or damage from microvascular thrombosis [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%